PERSONAL DATA PROTECTION IN THE EUROPEAN UNION UNDER THE TREATY OF LISBON - Viktoriya, Serzhanova (Anales Universitatis Apulensis Series Jurisprudentia; No 15 (2012): ANNALES UNIVERSITATIS APULENSIS - SERIES JURIPRDENTIA, 2013)
The paper aims at analyzing the present state of personal data protection in the European Union. It presents a general concept of personal data, origin and evolution of legal grounds for their protection, paying special attention to the changes in the provisions which were implemented by the Treaty of Lisbon. Later on it focuses on the activities of the European Data Protection Supervisor – an institution that aims at fulfilling the task of personal data protection in the EU. The paper discusses the appointing and recall procedure of the European Data Protection Supervisor, his legal status, position, duties, as well as the organization and functioning of the institution. Key words: personal data protection, the Treaty of Lisbon, the European Union, protection of human rights and freedoms, the right to privacy, the European Parliament